Red pizzas for a blue count. (New York : Scholastic, 2004)
Rodent newspaper writer Geronimo Stilton fears for his life when he is dragged off to Transratania, the land of vampire bats, on a mission to rescue his troublemaking cousin.
Translated from the Italian.
"Geronimo Stilton."
4.0
3-6
Keywords: Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Journalists -- Fiction; Cousins -- Fiction; Adventure and adventurers; Stilton, Geronimo (Fictional character) -- Fiction; Mice -- Fiction; Journalists -- Fiction; Cousins -- Fiction; Adventure fiction